Revolutionizing Brain Drug Delivery: Buccal Transferosomes on the Verge of a Breakthrough - Chandrasekhar, Pavuluri; Kaliyaperumal, Rajaganapathy (Recent Advances in Drug Delivery and Formulation, 2024)
The buccal cavity, also known as the oral cavity, is a complex anatomical structure that plays a crucial role in various physiological processes. It serves as a gateway to the digestive system and facilitates the initial stages of food digestion and absorption. However, its significance extends beyond mere digestion as it presents a promising route for drug delivery, particularly to the brain. Transferosomes are lipid-based vesicles that have gained significant attention in the field of drug delivery due to their unique structure and properties. These vesicles are composed of phospholipids that form bilayer structures capable of encapsulating both hydrophilic and lipophilic drugs. Strategies for the development of buccal transferosomes for brain delivery have emerged as promising avenues for pharmaceutical research. This review aims to explore the various approaches and challenges associated with harnessing the potential of buccal transferosomes as a means of enhancing drug delivery to the brain. By understanding the structure and function of both buccal tissue and transferosomes, researchers can develop effective formulation methods and characterization techniques to optimize drug delivery. Furthermore, strategic approaches and success stories in buccal transferosome development are highlighted, showcasing inspiring examples that demonstrate their potential to revolutionize brain delivery.
Keywords: Buccal drug delivery